2022
DOI: 10.1111/ijfs.15660
|View full text |Cite
|
Sign up to set email alerts
|

Study on the relationship between the degradation degrees of glutinous rice starch extruded with different α‐amylases and the qualities of Chinese rice wine

Abstract: SUMMARY In view that enzymatic extrusion can change the degradation degree of raw materials, this paper studied the regulation rules of four indexes of degradation degree of enzymatically extruded glutinous rice flour and the correlation between these indexes and the quality indexes of brewed Chinese rice wine. The results showed that at appropriate water content, dextrose equivalent (DE) and water solubility index (WSI) were linearly related to the enzyme content in extrusion with thermostable α‐amylase (TS‐α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Water absorption index (WAI) and water solubility index (WSI) were determined by the method of Guan et al (2022) with some modifications.…”
Section: Water Absorption Index and Water Solubility Indexmentioning
confidence: 99%
“…Water absorption index (WAI) and water solubility index (WSI) were determined by the method of Guan et al (2022) with some modifications.…”
Section: Water Absorption Index and Water Solubility Indexmentioning
confidence: 99%
“…Linko et al (1983) were the first to introduce α-amylase into a high-temperature, shorttime extruder, and they demonstrated that α-amylase exhibited higher activity in the extruder, resulting in accelerated liquefaction of starch. Guan et al (2022) applied enzymatic extrusion as a pretreatment method for rice starch and produced high-quality Chinese rice wine. Zhao et al (2022) found that enzymatic extrusion was beneficial for the fermentation of whole barley beer.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al . (2022) applied enzymatic extrusion as a pretreatment method for rice starch and produced high‐quality Chinese rice wine. Zhao et al .…”
Section: Introductionmentioning
confidence: 99%